Influences on birth spacing intentions and desired interventions among women who have experienced a poor obstetric outcome in Lilongwe Malawi: a qualitative study - Dawn M. Kopp; Agatha Bula; Suzanne Maman; Lameck Chinula; Mercy Tsidya; Mwawi Mwale; Jennifer H. Tang (BMC, 2018)
Abstract Background Stillbirth and neonatal mortality are very high in many low-income countries, including Malawi. Use of family planning to encourage birth spacing may optimize outcomes for subsequent pregnancies. However, reproductive desires and influences on birth spacing preferences of women who have experienced a stillbirth or neonatal death in low-resource settings are not well understood. Methods We conducted a qualitative study using 20 in-depth interviews and four focus group discussions with women who had experienced a stillborn baby or early neonatal death to explore attitudes surrounding birth spacing and potential interventions to promote family planning in this population. Qualitative data were analyzed for recurrent patterns and themes and central ideas were extracted to identify their core meanings. Results Forty-six women participated in the study. After experiencing a stillbirth or neonatal death, most women wanted to wait to become pregnant again but women with living children wished to wait for longer periods of time than those with no living children. Most women preferred birth spacing interventions led by clinical providers and inclusion of their spouses. Conclusions Many influences on family size and birth spacing were noted in this population, with the most significant influencing factor being the spouse. Interventions to promote birth spacing and improve maternal and neonatal health in this population need to involve male partners and knowledgeable health care providers to be effective. Trial registration Clinicaltrials.gov NCT02674542 Registered February 1, 2016 (retrospectively registered).